Effect of Health Education Using Animated Video Media and Snakes and Ladders Game on Young Girls’ Readiness for Facing Menarche - Solihatun Nisa; Fakrul Ardiansyah; H. Amandus; Revani Hardika (International Journal of Health and Pharmaceutical (IJHP), 2025)
Menarche is the first menstruation experienced by teenage girls. This period is a transitional period marked by various physical, emotional and psychosocial changes. Efforts to prevent the negative impact on menarche require knowledge about menstruation, one of which is using animated video media and snakes and ladders games. The aim of this research is to identify the influence of health education using the media game Snakes and Ladders and animated videos on the readiness of young women to face menarche. This type of research is quasi-experimental with pre and post test control group design. The research sample consisted of 40 female students using probability sampling with simple random sampling technique. Data analysis used the Paired T-Test and Independent T-Test. The results of the univariate test showed that the pre-test and post-test mean scores in the intervention group were 47.60 and 69.90 and the pre-test and post-test mean scores in the control group were 47.65 and 59.95. Bivariate analysis using the Paired T-Test in the intervention group and control group obtained a result of 0.000 where the p-value <0.05, meaning that there was an influence of health education using snakes and ladders game media and animated videos as well as powerpoint and leaflet media on the readiness of young women in facing menarche. The Independent T-Test showed a result of 0.000 where the p-value <0.05, meaning that there was a significant difference between the mean value of young women's readiness to face menarche in the intervention and control groups. The conclusion that can be drawn is that health education using the media game snakes and ladders and animated videos has an effect on the readiness of young women to face menarche. Animated video media and snakes and ladders games are more effective than PowerPoint and leaflet media in increasing the readiness of young women to face menarche.